Desenvolvimento de Metodologia Sintética Para a Síntese de Quinolonas Contendo Substituintes Triazólicos - Riscado, Cecília Schimming (2007)
Within the framework of research related to the chemistry of new substituted 4-oxoquinoline derivatives we decided to investigate an appropriate methodology for the synthesis of new 4-oxo-quinoline derivatives, containing the triazolyc nucleous as a substituent. α-carboethoxy-β-(3-nitrophenylamino)-ethyl acrylate (3a) and α-carboethoxy- β-(4-nitrophenylamino)-ethyl acrylate (3b) were synthesized. Thermic cyclization of these acrylates in Dowterm A led to the corresponding 3-carboethoxy-6-nitro-4-oxo-1,4- dihydroquinoline (14a) and 3-carboethoxy-7-nitro-4-oxo-1,4-dihydroquinoline (14b) in 79 and 78% yields, respectively. These nitro-oxo-quinolines were N-alkylated using ethyl bromide. Subsequent chemical reduction reaction produced 3-carboethoxy-1-ethyl-6- amino-4-oxo-1,4-dihydroquinoline (16a) and 3-carboethoxy-1-ethyl-7-amino-4-oxo-1,4- dihydroquinoline (16b) in 70% yield (16a) and 72% yield (16b). Diazotization reaction of 16a and 16b by using sodium nitrite and hydrochloric acid (36%) followed by sodium azide adition produced the new azido-oxo-quinolines 3-carboethoxy-1-ethyl-6-azido-4-oxo- 1,4-dihydroquinoline (17a; 83%) and 3-carboethoxy-1-ethyl-7-azido-4-oxo-1,4- dihydroquinoline (17b; 84%). Reaction between 17a and ethyl acetoacetate and acetylacetone gave the new desired compounds 1-etil-4-oxo-1,4-dihydro-6-carboethoxy-5- methyl-1H-[1,2,3-triazol-1-yl]-quinoline-3-carboxylic acid (18a2; 46%) and 1-ethyl-4-oxo- 1,4-dihydro-6-[4-acetyl-5-methyl-1H-[1,2,3]-triazol-1-yl]-quinoline-3-carboxilyc acid (19a; 48%). Also, the new pure acrylates α-carboethoxy-β-[4-(4-formyl-1H-[1,2,3]triazol-1- l)]phenylamino ethyl acrylate (11a) and α-carboethoxy-β-[3-(4-formyl-1H-[1,2,3]triazol-1- yl)]phenylamino ethyl acrylate (11b) were obtained in 100% yields both, by the following methodology: catalytic hydrogenation of 3a and 3b (Pd/C; ethyl alcohol; 4 atm) led to the corresponding amino derivatives 4a and 4b in 52% and 73% yields, respectively, followed by reaction with diazomalonaldehyde. Thermic ciclization of 11a e 11b in Dowtherm A, at 250ºC, for 5 minutes, produced the new pure triazol-1-yl-4-oxo-quinolines 12a (3- carboethoxy-6-(4-formyl-1H-[1,2,3]-triazol-1-yl)-4-oxo-1,4-dihydroquinoline) and 12b (3- carboethoxy-7-(4-formyl-1H-[1,2,3]-triazol-1-yl)-4-oxo-1,4-dihydroquinoline) in 58% and 31% yields, respectively.